(untitled) (Progressive Agriculture, 2018)
An experiment was conducted at the research field of the Department of Agricultural Botany, Patuakhali Science and Technology University, Patuakhali under the Agro-ecological zone-13 (AEZ-13) during the period from November 2012 to February 2013. The aim of the study was to identify the most effective irrigation level for obtaining the better growth and higher yield performance of BARI Gom-25 that are suitable to cultivate under coastal region of Patuakhali, Bangladesh. So, the present study was consists of five irrigations levels including control viz. control or no irrigation (T0), one irrigation at 25 DAS (T1), two irrigations at 25 and 40 DAS (T2), three irrigations at 25, 40 and 55 DAS (T3) and four irrigations at 25, 40, 55 and 70 DAS (T4). The seeds of BARI Gom-25 were collected from the BARI, Joydebpur, Gazipur on 22 November, 2012. The experiment was laid out in completely randomized block design (RCBD) with four replications and analysis was done by the MSTAT-C package program where means were separated by DMRT at 5% level of probability. Data were recorded on various growth and yield attributing traits. The plot size was 5 m2 (2.5 × 2.0 m) where row to row and seed to seed distances were 20 and 10 cm respectively. Data were collected on various morpho-physiological growth, yield and yield attributing traits. Results obtained from the present study, whole characters of the study were significant at 5% by the moisture (irrigation) levels where three irrigations given at 25, 40 and 55 DAS had most effective than that of other moisture levels and no irrigation. From the results investigation, it was found that the tallest plant (76.86 cm), maximum requiring days to anthesis (61.00 days), maturity (109.0 days) and maximum number of effective tillers (5.00 hill-1),the highest grain growth (3.11g at 36 DAA) and grains (44.00 spike-1) were obtained with three irrigation (T3) levels. Similarly, T3 further showed the greater performance on spike length (17.28 cm), 1000-seed weight (50.16 g), grain (4.16 t ha-1), straw (5.89 t ha-1) and biological yield (10.05 t ha-1) as well as the higher harvest index (41.39%). Investigated above whole characters were produced lower performances under no moisture (irrigation) treatments. These results indicated that irrigation at three times (T3) would be most advantageous irrigation levels for wheat production under the studied non saline ecosystem of coastal region. Progressive Agriculture 29 (2): 99-106, 2018